The incidence of dental caries in indigent Filipino children with cleft lip and/or palate (CLAP) from the Noordhoff Craniofacial Foundation Philippines, Incorporated (NCFPI) - Ildefonso, Eula C.; Palabrica, Maria Blanca; Tuaño-Cabrera, Cecile P.
One in every 500 children born in the Philippines is diagnosed with cleft lip and/or palate (CLAP). Dental anomalies which arise in relation to the defect along with restrictions in oral hygiene are considered to be predisposing factors to the development of dental caries. However, there are hardly any studies which focus on the needs and conditions of these patients. This study aims to provide an overview and statistical data on the incidence of dental caries in Filipino children which can be used by dental health care professionals (DHCPs) as a guide in imparting the necessary oral hygiene instructions to the parents and caregivers of the patient to lessen pre-surgical treatment in other cases of CLAP in the future.
A retrospective quantitative descriptive study was carried out based on treatment records of children ages 2-12 with CLAP from 2009-2012 under the Noordhoff Craniofacial Foundation Philippines (NCFPI), in partnership with Pediatric Dentistry Center of the Philippines (PDCP). Statistical data on incidence of dental caries in relation with age, sex and type of oral cleft were collected and analyzed from 332 records.
The incidence of caries in children with oral cleft from 2009-2012 is 0.81 from dmft and 0.37 for DMFT. No significant difference in caries Incidence among different cleft types was found. However, the caries incidence among the 10-12 age group was found to be the highest.
It has been found that CLAP patients have a high caries incidence (0.81dmft abd 0.37 DMFT). Poor oral hygiene and the presence of other predisposing factors can increase the susceptibility of such population to the progression of caries. Among these predisposing factors are developmental anomalies and oral habits such as nighttime bottle feeding, thumb sucking and mouth breathing.
Thesis--(Doctor of Dental Medicine)--University of the Philippines Manila
Keywords: Dental caries; Filipino children; Cleft lip; Cleft palate